Pneumocystis jirovecii Pneumonia Mimicking COVID-19 Pneumonia in a Patient with Newly Diagnosed Advanced HIV Disease - Ahmad Anwaar Muhammad Saifullah; Nour Hanan Daniah Mohd Bakhit; Assyifaa Nik Mazian; Sarah Zulaikha Samad; Nor Safiqah Sharil; Siow Kim Yoon; Mohd Rahman Omar (USIM Press, 2024)
ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences (Special Issue IHEC 01-2021) [April 2021]